Analyzing the Syntactic Patterns of Gen Z English: The Use of Non-Standard Sentence Structure in Digital Discourse - Dhea Salsabila; Nasywa Faira; Ade Aisyah Nazhwandini; Dini Aghnianty Harahap; Siti Ismahani (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the distinctive syntactic patterns found in Gen Z English, particularly as they appear in digital communication across platforms such as TikTok comments, Twitter threads, Instagram captions, and personal chats. Drawing on examples including “so done,” “me when I see food,” “she kinda cute,” and “staying delulu is the solulu,” the research analyzes how fragment clauses, subject and auxiliary omission, meme-based constructions, and playful morphological innovations shape the linguistic style of contemporary youth discourse. Using a qualitative descriptive approach, the study identifies non-standard sentence structures, describes recurring syntactic patterns, and explores the influence of social media, meme culture, and digital register on their formation. The findings reveal that these forms, while structurally unconventional, function effectively within digital contexts and contribute to emerging shifts in Modern English. The study concludes that Gen Z English reflects not linguistic decay but a dynamic linguistic evolution driven by creativity, efficiency, and social identity.